Mysticism of the Earth according to thought of Christian East - Aptacy, Janusz (Studia Ecologiae et Bioethicae, 2005)
This article is an attempt at showing reflection of Christian East concerning nature, earth and the world as a manifestation of Gods creative Will. The world according to this science is not an ordinary emanation of a Deity or an arranging of the former existing matter by some creator, as Greek philosophers claimed. The world appears to be something brand new, created “out of nothing” (ex nihilo). It is wanted and loved by God. God expresses Himself by the world and gives to all the beings which we can see only as material ones a deep sense and spiritual meaning as well. God, through the world, expresses Himself in a way understandable for a human being. Consequently, human being has got a special task; he should discover this sense and this meaning present in the beings created, so as to make communication between him and God possible. Human being, as “a priest and a guardian of the Universe” owing to spiritual sight, owing to spiritual “fire eyes” penetrating the depth of creatures and things, has to discover and show this meaning. The sense, the meaning (logoi) of all that exists has got its own foundation and fulfilment only in the Supreme Divine Logos.